Tales of gotham, historical archaeology, ethnohistory and microhistory of New York City - Dallal, Diane; Janowitz, Meta F. (Springer New York, 2013)
Historical Archaeology and Ethnohistory of New York City: Tales and Microhistory of Gotham is a collection of narratives about people who lived in New York City during the seventeenth, eighteenth, and nineteenth centuries, people whose lives archaeologists have encountered during excavations at sites where these people lived or worked. The stories are ethnohistorical or microhistorical studies created using archaeological and documentary data. As microhistories, they are concerned with particular people living at particular times in the past within the framework of world events.    The world events framework will be provided in short introductions to chapters grouped by time periods and themes. The foreword by Mary Beaudry and the afterword by LuAnne DeCunzo bookend the individual case studies and add theoretical weight to the volume. Topics in the book include: ·         Native Americans and Europeans in New Amsterdam ·         Stories of Dutch women in the colonial period ·         African history in New York City, including the African Burial Ground ·         Craftsmen and Churchmen of New York City ·         A portrait of Stephen Allen, a New York City Mayor  Historical Archaeology and Ethnohistory of New York City: Tales and Microhistory of Gotham focuses on specific individual life stories, or stories of groups of people, as a way to present archaeological theory and research. Archaeologists work with material culture-artifacts-to recreate daily lives and study how culture works; this book is an example of how to do this in a way that can attract people interested in history as well as in anthropological theory. As such, this volume is an invaluable resource for archaeologists, historians, ethnographers, anthropologists, and anybody interested in the rich history of one of the world's most influential cities, New York City.